Staging Investigations in Asymptomatic Early Breast Cancer Patients at the Cancer Centre of Southeastern Ontario - Dalia Kamel; Veronica Youssef; Wilma M. Hopman; Mihaela Mates (Current Oncology, 2021)
Background: In 2012, the American Society for Clinical Oncology (ASCO) identified five key opportunities in oncology to improve patient care, recommending against imaging tests for the staging of patients with early breast cancer (EBC) at low risk for metastases. Similarly, the European Society of Medical Oncology (ESMO) guideline does not support radiological staging in asymptomatic EBC (aEBC). The purpose of this study was to assess local practice and outcomes of staging investigations (SIs) in aEBC at the Cancer Centre of Southeastern Ontario (CCSEO). Methods: A retrospective electronic and paper chart review was undertaken to identify all aEBC patients treated at our institution between January 2012 and December 2014. Patients with pathological staging of T1-T2 and N0-1 with any receptor status were included. We collected patient demographics, treatment and pathologic tumor characteristics. The use and outcomes of initial and follow-up SIs were recorded. Data were analyzed to determine associations between the use of SIs and clinical characteristics (chi-square tests, independent samples t-tests and Mann–Whitney U tests). Results: From 2012 to 2014, 295 asymptomatic EBC patients were identified. The mean age was 64, 81% were postmenopausal and 76% had breast conserving surgery. Stage distribution was as follows: stage I 42%, stage IIA 37% and stage IIB 21%. Receptor status was as follows: ER+ 84%, HER2+ 13% and triple negative 12%. Adjuvant chemotherapy was received by 36%, Trastuzumab by 10% and endocrine therapy by 76% of patients. Baseline SIs were performed in 168 patients (57%) for a total of 332 tests. Overt metastatic disease was found in five patients (one bone scan and four CT scans). Seventy-one out of the 168 patients (42%) who received initial staging imaging underwent 138 follow-up imaging tests, none of which were diagnostic for metastases. Nine patients with suspicious CT findings underwent biopsies, of which four were malignant (one metastatic breast cancer and three new primaries). Factors significantly associated with SI were as follows: younger age (p = 0.001), premenopausal status (p = 0.01), T2 stage (p < 0.001), N1 stage (p < 0.001), HER2 positive (p < 0.001), triple negative status (p = 0.007) and use of adjuvant chemotherapy (p < 0.001). Conclusions: Over a 3-year period at our institution, more than 50% of aEBC patients underwent a total of 470 initial and follow-up staging tests, yielding a cancer diagnosis (metastatic breast cancer or second primary cancer) in four patients. We, therefore, conclude that routine-staging investigations in aEBC patients have low diagnostic value, supporting current guidelines that recommend against the routine use of SI in this population.